Mediterranean Shrubs: Nutraceuticals for sustainable goat production - Costa, Cláudia (2020)
Mediterranean Shrubs: Nutraceuticals for sustainable goat production Costa, C.ab, Almeida, S.M.c, Cavaco-Gonçalves, S.a, Barbas, J.P.a, Ribeiro, J.M.B.F.a, Belo, C.C.a, Padre, L.b, Belo, A.T,a aINIAV, Santarém – National Institute of Agrarian and Veterinarian Research, Quinta da Fonte Boa, 2005-048 Vale de Santarém bICAAM – Department of Veterinary Medicine, Évora University, Pólo da Mitra, 7006-554 Évora cUTAD – Trás-os Montes and Alto Douro University, Quinta de Prados, 5000-801 Vila Real E-mail: anateresa.belo@iniav.pt Bioactive natural products have become an important research topic and development area in different fields of study, owing to their numerous potentialities. In animal production, the anthelminthic, antioxidant and antimicrobial properties of natural vegetation can improve the animals’ productive efficiency and wellbeing, and product quality (meat and milk). It is known that goats have a very selective feeding behavior and a higher sensitivity to gastrointestinal strongyles (GIS) infections compared to other ruminants, and that certain plants have beneficial effects in animal health through the synergy between their nutritive value and bioactive compounds. Thus, the project “VegMedCabras” intends to characterize and explore the nutraceutical value of mediterranean shrubs for sustainable goat production, by controlling parasitic infection as well as preventing environmental contamination and residues in the final product from the continuous use of synthetic anthelmintics [1,2,3]. Charnequeira breed goats were observed during browsing/grazing of Mediterranean vegetation, from February to July, in order to document their shrub species preferences and evaluate the nutraceutical value of the final diets. All selected plants were analyzed for nutritive value (protein and fiber content, digestibility), as well as bioactive compounds content such as total phenolic compounds (TPC), total tannins (TT), condensed tannins, flavonoids and saponins. Antioxidant activity was also evaluated. Each goat was individually evaluated for natural GIS infection, by egg elimination levels, and health status, by metabolic blood parameters. A significant drop in EPG (eggs per gram of feces) elimination (± 65%) was observed by the end of the study period. As soon as goats started browsing the Mediterranean vegetation, EPG counts started to decrease as the proportion of shrubs rich in TPC increased in the diet. Species with the highest contribution were Pistacia lentiscus and Quercus coccifera, which presented an average TPC and TT of 163,6 and 134,2 mg GAE (gallic acid equivalent)/g MS vs. 138,4 and 130,2 mg GAE/g MS, respectively. Nutritive value of the diets selected by goats was estimated in order to determine the adequacy to their physiological requirements. With the increased resistance of GIS to synthetic anthelmintics and social demand for quality products, it is important to establish multidisciplinary options such as the use of nutraceutical shrubs, a safer, ecological and inexpensive solution. Keywords: nutraceuticals; Mediteranean shrubs; bioactive compounds; anthelmintics; goats References: [1]. Jasmim RS (2018) Int. J. Botany 14: 24-29. [2]. Saric T, Rogosic J, Zupan I, Beck R, Bosnic S, Sikic Z, Skobic D, Tkalcic S (2015) Small Rum. Res. 123: 179-182. [3]. Hoste H, Torres-Acosta JFJ, Sandoval-Castro CA, Muller-Harvey I, Sotiraki S, Louvandini H, Thamsborg SM, Terrill TH (2015) Vet. Parasitology 212: 5-17. Acknowledgements: VegMedCabras – Mediterranean shrubs: natural anthelmintics in the diet selected by grazing goats (ALT-03-0145-FEDER-000009) co-financed by ALENTEJO2020 program-European Regional Development Fund.